CRITICAL REVIEW OF ETHNOGRAPHIC APPROACH - Lusia Marliana Nurani (Jurnal Sosioteknologi, 2008)
There are two basic characteristics of ethnography: (1) the observation takes place in natural setting, (2) researchers must understand how an event is perceived and interpreted by the people in a speech community. In other words, the researchers try to interpret the situation being observed from the perspective of the participants. Ethnography also relies on observations of interactions and interviews with participants in naturally occurring situation. The next characteristic of ethnography is the characteristic of "holistic" which means seeing the data as a whole in order to get a basis for explanation about the observable fact. Another characteristic is that ethnographic approach does not formulate the hypothesis prior to the research. The hypothesis will emerge as the data collection occurs. Ethnographic research has one main drawback related to reliability. It is difficult to replicate ethnographic research because an event in natural setting cannot be reproduced. There is also one main problem dealing with validity. Unlike another research where the researcher can maximally control external variables, the ethnographic research does not have this facility because the research is carried out in natural setting and due to the long time period of observation. Despite the limitations of the ethnographic approach, it has benefits for research in naturalistic setting such as class room research, language learning process in a particular speech community, and so forth because the finding is more real than a research that manipulates variables by using external experiments. Key words: ethnography, observation, natural setting